2016
DOI: 10.1002/jmri.25177
|View full text |Cite
|
Sign up to set email alerts
|

Detecting gas‐induced vasomotor changes via blood oxygenation level‐dependent contrast in healthy breast parenchyma and breast carcinoma

Abstract: PurposeTo evaluate blood oxygenation level‐dependent (BOLD) contrast changes in healthy breast parenchyma and breast carcinoma during administration of vasoactive gas stimuli.Materials and MethodsMagnetic resonance imaging (MRI) was performed at 3T in 19 healthy premenopausal female volunteers using a single‐shot fast spin echo sequence to acquire dynamic T 2‐weighted images. 2% (n = 9) and 5% (n = 10) carbogen gas mixtures were interleaved with either medical air or oxygen in 2‐minute blocks, for four complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…D YNAMIC CONTRAST-ENHANCED magnetic resonance imaging (DCE-MRI) is the backbone of any given MRI protocol, but to address limitations in specificity and to improve breast cancer diagnosis, a plethora of functional MRI parameters, ie, diffusion-weighted imaging (DWI), proton and phosphorus MR spectroscopy, sodium imaging, blood oxygenation level-dependent imaging, and chemical exchange saturation transfer imaging are being investigated. [1][2][3][4][5][6][7] In this context, DWI with apparent diffusion coefficient (ADC) mapping is one of the most useful MRI parameter and is now often used in a multiparameric imaging setting for breast cancer detection. 2,5,8,9 DWI with ADC mapping provides information on tissue microstructure and cellularity that can be used for lesion characterization.…”
mentioning
confidence: 99%
“…D YNAMIC CONTRAST-ENHANCED magnetic resonance imaging (DCE-MRI) is the backbone of any given MRI protocol, but to address limitations in specificity and to improve breast cancer diagnosis, a plethora of functional MRI parameters, ie, diffusion-weighted imaging (DWI), proton and phosphorus MR spectroscopy, sodium imaging, blood oxygenation level-dependent imaging, and chemical exchange saturation transfer imaging are being investigated. [1][2][3][4][5][6][7] In this context, DWI with apparent diffusion coefficient (ADC) mapping is one of the most useful MRI parameter and is now often used in a multiparameric imaging setting for breast cancer detection. 2,5,8,9 DWI with ADC mapping provides information on tissue microstructure and cellularity that can be used for lesion characterization.…”
mentioning
confidence: 99%
“…This is synthesized in a hypoxic environment to counteract the effects of the tissue oxygen deprivation changing the threshold, at which hypoxia might be considered pathological. Also, breast tissue has a complex architecture and a variable oxygen demand due to background physiological fluctuations secondary to menstrual cycle changes [8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that BOLD MRI may aid patient stratification for hypoxia-targeted therapies and has potential to provide early predictive response monitoring. Other studies in the breast have shown that 100% oxygen interleaved with carbogen (5% CO 2 , 95% O 2 ) in a block design is the optimal stimulus for inducing BOLD contrast (Rakow-Penner et al 2010 , Wallace et al 2016a ). Carbon dioxide is a potent vasodilator and the opposing effects of these two gases on vascular tone provide a mechanism for BOLD contrast, which is also sensitive to changes in blood volume and flow.…”
Section: Introductionmentioning
confidence: 99%